Corporate Criminal Liability for Cybersecurity: Rechtsvinding in Adopting the Concept of Corporate Manslaughter in Indonesia - Mangkunegara, RM. Armaya (Badan Pembinaan Hukum Nasional, 2025)
The rapid development of digital technology presents significant challenges to the criminal justice system, particularly in relation to cybercrimes involving corporations. In Indonesia, the corporate criminal liability system has yet to fully address the complexities of these crimes, such as data breaches and cyberattacks. This study aims to analyze the role of rechtsvinding as a methodological foundation for updating the corporate criminal liability model and to identify the challenges and opportunities in implementing the concept of corporate manslaughter in Indonesia. The research adopts a normative-qualitative approach with literature review and international legal comparison. The findings show that rechtsvinding can bridge the legal gaps through innovative interpretations, while the adoption of corporate manslaughter offers a new paradigm in assessing corporate negligence. However, its implementation faces regulatory, cultural, and evidentiary challenges that need strengthening. The study recommends the harmonization of regulations and the enhancement of law enforcement capacity to ensure effective implementation, thereby supporting corporate accountability and the protection of individual rights in the digital era.